2020
DOI: 10.22323/2.19010208
|View full text |Cite
|
Sign up to set email alerts
|

Gender-biased public perception of STEM fields, focusing on the influence of egalitarian attitudes toward gender roles

Abstract: Many studies have examined the impression that the general public has of science and how this can prevent girls from choosing science fields. Using an online questionnaire, we investigated whether the public perception of several academic fields was gender-biased in Japan. First, we found the gender-bias gap in public perceptions was largest in nursing and mechanical engineering. Second, people who have a low level of egalitarian attitudes toward gender roles perceived that nursing was suitable for women. Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Previous findings have shown that students are aware of racial and gender disparities in STEM and often attribute these inequities to racism and discrimination (Hanson, 2009;Lewis Ellison et al, 2020). For instance, Ikkatai et al (2020) found that 61% of the high-school, undergraduates, and graduate students they surveyed reported experiencing gender bias in their math or science classes from peers or teachers. In considering the perceptions and experiences of Black girls, MARTIN AND FISHER-ARI | 1079 Hanson (2009) found that study participants reported a lack of representation of Black scientists and teachers within their science classrooms and often experienced isolation, ignoring, and lack of confidence about their abilities to do science.…”
Section: High-school Students and Experiences With Science And Stemmentioning
confidence: 99%
“…Previous findings have shown that students are aware of racial and gender disparities in STEM and often attribute these inequities to racism and discrimination (Hanson, 2009;Lewis Ellison et al, 2020). For instance, Ikkatai et al (2020) found that 61% of the high-school, undergraduates, and graduate students they surveyed reported experiencing gender bias in their math or science classes from peers or teachers. In considering the perceptions and experiences of Black girls, MARTIN AND FISHER-ARI | 1079 Hanson (2009) found that study participants reported a lack of representation of Black scientists and teachers within their science classrooms and often experienced isolation, ignoring, and lack of confidence about their abilities to do science.…”
Section: High-school Students and Experiences With Science And Stemmentioning
confidence: 99%
“…According to the results of the survey, the mean scores of male students STEM -A were higher than those of female students STEM -A. Many studies (Ciftci, Topcu, & Erdogan, 2020;Ikkatai et al, 2020;Makarova, Aeschlimann, & Herzog, 2019;Sadler et al, 2012) indicated that female and male students have different attitudes toward science, technology, engineering, and mathematics and supported the result of the research. The studies showed that male students have more interest in STEM fields than female students.…”
Section: Discussionmentioning
confidence: 68%
“…Biased perceptions of gender roles will cause people to think gender-biased as well. In a study of general public perceptions of 18 fields of academic work in Japan, it was revealed that nursing was considered a good job for women, whereas mechanical engineering was not considered a good job for women [11]. They show that there are still some people with the stereotypical view that science is good for men, but not for women.…”
Section: Limitations Of Developing For Womenmentioning
confidence: 99%